Meta Analisis: Efektivitas Diet DASH terhadap Penurunan Tekanan Darah pada Penderita Hipertensi - Lindsay Ozora Sanyaezra Simanjuntak (Pusat riset dan Inovasi Nasional, 2026)
Background: Hypertension is a global health issue that significantly contributes to morbidity and mortality. The DASH diet (Dietary Approaches to Stop Hypertension) has been recommended as a dietary approach to lower blood pressure, but findings across studies remain varied. Therefore, a meta-analysis was conducted to synthesize the existing evidence on the effectiveness of the DASH diet for blood pressure reduction in hypertensive patients. Objective: To systematically and quantitatively assess the effect of the DASH diet on lowering blood pressure in individuals with hypertension. Methods: This meta-analysis employed a random-effects model using Standardized Mean Difference (SMD) as the effect size. Data were extracted from six studies that met the inclusion criteria. OpenMEE software was used to calculate the pooled effect estimate and inter-study heterogeneity. Results: The findings showed that the DASH diet significantly reduced blood pressure, with an SMD of -1.219 (95% CI: -1.918 to -0.519; p < 0.001). Substantial heterogeneity was found across the included studies (I² = 88.24%; p < 0.001), indicating variations in population characteristics and study methodologies. Conclusion: The DASH diet is effective in lowering blood pressure in hypertensive patients and can be considered a key component of non-pharmacological intervention strategies. Despite the presence of heterogeneity, the consistent direction of effect supports its broader implementation with individual adaptations.